2020
DOI: 10.1038/s41438-020-00352-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing and population genomics modeling provide insights into the local adaptation of weeping forsythia

Abstract: Understanding the genetic basis underlying the local adaptation of nonmodel species is a fundamental goal in evolutionary biology. In this study, we explored the genetic mechanisms of the local adaptation of Forsythia suspensa using genome sequence and population genomics data obtained from specific-locus amplified fragment sequencing. We assembled a high-quality reference genome of weeping forsythia (Scaffold N50 = 7.3 Mb) using ultralong Nanopore reads. Then, genome-wide comparative analysis was performed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 83 publications
2
41
0
Order By: Relevance
“…However, which pathways and ontologies are associated with heterogeneous drought stress can be detected by identifying candidate SDGs in twenty weeping forsythia populations. A total of 1,269 candidate SDGs involved into drought adaptation were identified by LFMM in previous studies [ 15 ]. Through enrichment analysis of SDGs in natural weeping forsythia populations, the ontologies related to the synthesis of aromatic substances (Table 3 ), such as farnesyl diphosphate metabolic process, sesquiterpene biosynthetic process, germacrene-A synthase activity, and sesquiterpene synthase activity, has undergone sequence differentiation in response to heterogeneous drought stress.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, which pathways and ontologies are associated with heterogeneous drought stress can be detected by identifying candidate SDGs in twenty weeping forsythia populations. A total of 1,269 candidate SDGs involved into drought adaptation were identified by LFMM in previous studies [ 15 ]. Through enrichment analysis of SDGs in natural weeping forsythia populations, the ontologies related to the synthesis of aromatic substances (Table 3 ), such as farnesyl diphosphate metabolic process, sesquiterpene biosynthetic process, germacrene-A synthase activity, and sesquiterpene synthase activity, has undergone sequence differentiation in response to heterogeneous drought stress.…”
Section: Resultsmentioning
confidence: 99%
“…Although weeping forsythia is a drought-tolerant medicinal crop, long-term drought stress will affect its growth and fruit production. Recently, the genome sequence of weeping forsythia has been published, which provides opportunities for us to explore the genetic mechanisms of local adaptation [ 15 ]. Past studies using population genomics focused on detecting and quantifying adaptive differentiation in gene sequences in response to drought stress among different natural populations [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One emerging question is why there are so many TFBS genetic variants. Because the natural selection exerted by environmental factors contributes substantially to the population genetic structure [64], one prominent hypothesis is that TFBS variants arise from natural selection and facilitate human adaptation to the local environment. Several theories suggest that TFBS sequences may be particularly important in evolutionary adaptation.…”
Section: Origin Of Tfbs Genetic Variants: Natural Selectionmentioning
confidence: 99%
“…Divergent selection is one of the most important fundamental evolutionary processes for genetic differentiation among populations, and further facilitates reproductive isolation among populations and completes speciation (Thompson, 2016;Bamba et al, 2019;Li J. L. et al, 2020). Numerous studies of plants have found that understanding local population adaptations could not only provide more information on how populations respond to divergent ecological factors but could also provide farreaching implications for species management, conservation, and ability to cope with global climate change (Fady et al, 2016;LĂĄzaro-Nogal et al, 2016;Rellstab et al, 2016;Escalante et al, 2020;Li L.-F. et al, 2020;Moran, 2020). The consequences and mechanisms of balancing selection in plants have seldom been addressed due to the partial or lacking genomic investigation of plant populations (Zou et al, 2017), with the exception of information on biotic interactions such as sex-determining alleles among model plants (Weis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%